Enhancing Learning Activities and Learning Outcomes in Quran and Hadith Education through Audio-Visual Media - Silvi Oktariani; Ardi Satrial; Taruddin Taruddin; Sarah Rahmayani; Syahrul Ramadhan; Inong Satriadi; Mowafg Abrahem (International Journal of Islamic Teaching and Learning, 2026)
This study aims to examine the implementation of audiovisual media and its impact on improving learning outcomes in Quran and Hadith education among ninth-grade learners at an Islamic boarding school in Indonesia. The study employed the Kemmis and McTaggart Classroom Action Research model, conducted over two cycles consisting of planning, implementation, observation, and reflection. The participants were 25 ninth-grade learners during the 2025/2026 academic year. Data were collected through structured classroom observations and learning outcome tests and analyzed using descriptive quantitative techniques. The findings indicate that the integration of laptop- and projector-based instructional videos increased learner participation and classroom engagement throughout the learning process. Learners' average achievement improved from 75.20 (36% mastery) in the first session to 87.40 (100% mastery) in the fourth session. These findings demonstrate that the systematic integration of audiovisual media effectively enhances both classroom engagement and learning outcomes in Quran and Hadith education. The study contributes empirical evidence supporting the use of audiovisual media as an instructional strategy in Islamic boarding school contexts.